Analysis of Land Cover Change in Aik Berik Village Area, Central Lombok Regency - Anis, Anis Syakiratur Rizki; Mulyaningsih, Tri; Propita Lestari, Dinda; Primaditya Hasanto, Rizki (Journal of Microbiology, Biotechnology and Conservation, 2025)
Land cover change in tourist areas is often an important issue related to the impact of human activities on the environment. This study aims to analyze land cover changes in the Aik Berik Village area, Central Lombok Regency, by utilizing remote sensing technology and Geographic Information System (GIS). Multitemporal satellite image data is used to identify types of land cover, such as forests, agricultural land, built land, and open land, over a period of time. Spatial analysis is carried out to determine the pattern of change and the factors that affect it. The results of the analysis showed that there was a significant change in land conversion, with the conversion of forest areas into plantations, rice fields, and built-up land. Despite this, most of the forest area has been preserved thanks to natural regeneration factors and community-based management. In addition, some plantation areas have changed their function to rice fields and built land, while savanna areas are relatively stable. These changes have the potential to affect the quality of ecosystems and the hydrological cycle of the region. The success of Aik Berik Village in maintaining forests and springs that are vital to the community shows the importance of sustainable and community-based land management.